Improving Women's Mental Health during a Pandemic - Ahmed, Firoz; Islam, Asad; Pakrashi, Debayan; Rahman, Tabassum; Siddique, Abu; Vlassopoulos, Michael (American Economic Journal: Applied Economics, 2024)
This paper evaluates a randomized, over-the-phone counseling intervention aimed at mitigating the mental health impact of COVID-19 on a sample of 2,402 women across 357 villages in Bangladesh. We find that the provision of two hours of mental support plus information on COVID-19 improves mental health ten months postintervention, leading to reductions of 20 percent in the prevalence of moderate and severe stress and 33 percent in depression. Our results suggest that this type of low-cost intervention (
Keywords: Human Development; Income Distribution; Migration; Non-labor Discrimination, Microeconomic Analyses of Economic Development, Economic Development: Human Resources; Health; Health Behavior, Health: Government Policy